Le elezioni presidenziali in Ucraina: vince il candidato Zelensky con oltre il 73% dei consensi (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2019)
The recent presidential elections in Ukraine determined the victory of the comedian Volodymyr Zelensky, whose electoral campaign was focused on the fight against corruption. Nevertheless, Zelensky has not showed a clear position on the secession of Crimea.
Keywords: Ukraine; parliamentaryelections; Zelensky